Isolation and Purification of Intact Peroxisomes from Green Leaf Tissue - Schmitt, Mark R. (1982)
Intact peroxisomes were prepared from green leaves of a number of C(3) species, both monocots and dicots. A protoplast extract from which chloroplasts have been removed by a 1-minute 10,000g centrifugation was applied to a step gradient of 5, 15, 30, and 45% Percoll containing 0.5 molar sucrose, 0.1% BSA, and 25 millimolar Hepes-KOH (pH 7.5). After centrifugation, a peroxisomal fraction with low contamination by chloroplastic and mitochondrial markers was recovered from the 30/45% Percoll interface. This fraction was passed through a Sepharose 2B column to remove the Percoll which resulted in a peroxisomal preparation exhibiting high intactness (estimated from enzyme latency) and stability.